KOMPUTERISASI TABEL SIFAT-SIFAT TERMODINAMIK DARI H2O, R-12, DAN R-22 (PROTAMIK) - Khuriati RS, Ainie; Detika, Detika; Bawono P, Ari (BERKALA FISIKA, 2013)
A computer program has been created which is used to display the thermodynamic properties (T, p, v, u, h, and s) of the working fluid of the commonly used on the power generation and processindustries,  H2O, R-12, and R-22. It  also calculates  the thermodynamic properties as function of  saturationtemperature and quality and saturation  pressure and quality. Program was developed using the thermodynamic properties of steam properties from 1967 ASME Steam Table [1] andASHRAE tables [5].Keywords: thermodynamics, properties, steam tables, refrigerant tables, quality.